SUSTAINABLE TRANSPORT IN MOROCCO: WHAT CONTINGENCY FACTORS FOR WHICH MATURITY LEVEL? CASE OF ROAD HAULAGE “RH” SERVICE PROVIDERS IN THE REGION OF CASABLANCA METROPOLIS - Elhasbi, Abbes; Jami, Jihad; Kammas, Said (European Scientific Journal, ESJ, 2015)
Dealing with sustainable transport has allowed researchers and practitioners to suggest several solutions (decoupling, inter-modality…) capable of providing, at least, part of the answers to the negative externalities caused by road haulage. Traffic congestion, sound nuisance, pollution, insecurity… are so many effects produced by the overuse of heavy goods vehicles. As regards sustainable development, Morocco has demonstrated its firm commitment to include this variable, in order to ensure an economic growth less subject to climatic vagaries, cope with energy crises and reduce the social costs. Thus, it was not until through the logistical competitiveness strategy in Morocco (program contract 2010-2015) that clear objectives and action plan related to investing and trading, as part of sustainable transport, have been set. The objective of this publication is to evaluate sustainable development practices of the road haulage service providers and the study of the contingency factors revealing these practices. Given that it constitutes an economic hub par excellence at the national level and a nodal point as regards trading flows, whether it be with regard to national or international transport, we have chosen the region of Greater Casablanca (Morocco) as the empirical field of study.